A new feminist ethic that unites and mobilizes people: the participation of young people in Argentina's Green Wave. Issue 2 (2nd September 2021) - Artazo, Gabriela; Ramia, Agustina; Menoyo, Sofia
ABSTRACT: The year 2021 began with good news: on 29 December 2020, the law that guarantees access to the right to legal, safe and free abortion was approved in Argentina's National Congress and Senate. This achievement was the result of the struggles of the feminist and women's movement. A particular feature was the massive involvement of young people in discussions, street mobilisations and vigils, with all those taking part wearing green bandanas, the movement being named the 'Green Wave' (Marea Verde), as a result. After the law was passed, the organisation Catholics for the Right to Decide (CDD), an active member of the National Campaign for the Right to Legal, Safe and Free Abortion – with the support of the Global Fund for Women – asked us to investigate the role and participation of young people from different parts of our country in the Green Wave movement. This article discusses the findings of this research project.